SOCIAL STUDIES EDUCATION AS A MEANS FOR COMBATING SOCIAL PROBLEMS IN NIGERIAN SECONDARY SCHOOL - Abdul Kabir, Asmau Imam (Journal of Techno-Social, 2014)
The purpose of education in Nigeria as in many other developing countries is the preparation of the individual to contribute to the development of the nation and for the transmission of the social and cultural values to new generations. Yet, the Nigerian society has been surrounded by an array of political, economic, and social crises. For this reason, Social Studies is assigned the responsibility to develop in Nigerian youth an understanding of their societal values, knowledge, values, and skills that would enable them to deal with and manage the forces of the world in which they live, and learn how to live harmoniously in the society. This study examines the contents and purposes of the Social Studies education with special reference to its ability to instil high-quality moral values and good character in students and provide them the necessary skills, abilities, and competencies, which individual students require to participate in the development of the nation. It is recommended among others the need for a thorough review of the Social Studies curriculum with emphasis on moral inculcation.